Evaluation of the SARS-CoV-2 infection rate in patients undergoing Total Hip Arthroplasty by the Anterior Approach using a Rapid Recovery Protocol during a COVID-19 pandemic in a Public Hospital in the State of São Paulo - Marco Aurélio Silvério Neves; Victor Edmond Seid; Leandro Gregorut Lima; Gustavo Rocha Santos; Dimas Vicente Terra Santos; Bruno da Silva Ivo; Ivan Espuri; Barbara Fialho Carvalho Sampaio (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
The World Health Organization (WHO) declared, on January 30, 2020, that the outbreak of the disease caused by the new Coronavirus (COVID-19) constitutes a Public Health Emergency of International Importance - the highest level of alert of the Organization, as provided for in the International Health Regulations. On March 11, 2020, COVID-19 was characterized by the WHO as a pandemic and since then the world has been going through an unprecedented period. The pandemic is interfering with all aspects of everyday life, especially in the area of ​​health. Surgical practice was directly affected by the suspension of elective procedures and the prioritization of urgent and emergency surgeries as a way to free up beds for patients infected with the disease. New coronavirus. The script for resumption of elective surgery after this COVID-19 pandemic must be progressive and cautious. Elective surgery should be performed in COVID-free facilities and the hospital stay should be as short as possible. For safety reasons, patients considered for surgery should be carefully selected according to status/exposure to COVID-19 infection, age, ASA physical status/risk factor classification system, socio-professional status and surgical indication. Therefore, in this study, we will demonstrate the positive impact on surgical resumption using a rapid recovery protocol combined with a minimally invasive technique (AMIS) for total hip arthroplasty during the period of worldwide pandemic for SARS-CoV-2.